2016
DOI: 10.1007/s11606-016-3789-9
|View full text |Cite
|
Sign up to set email alerts
|

Case Management may Reduce Emergency Department Frequent use in a Universal Health Coverage System: a Randomized Controlled Trial

Abstract: BACKGROUND: Frequent emergency department (ED) users account for a disproportionately high number of ED visits. Studies on case management (CM) interventions to reduce frequent ED use have shown mixed results, and few studies have been conducted within a universal health coverage system. OBJECTIVE: To determine whether a CM intervention--compared to standard emergency care-reduces ED attendance. DESIGN: Randomized controlled trial. PARTICIPANTS: Two hundred fifty frequent ED users (5 or more visits in the prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(119 citation statements)
references
References 37 publications
(57 reference statements)
4
114
0
1
Order By: Relevance
“…The high heterogeneity between studies, most importantly in how frequent users are defined, but also in participant demographic and clinical characteristics, the nature of the intervention (type and quality of case management) and system level-factors such as availability and accessibility of usual care services, may contribute to the lack of consistent findings and certainly limits the ability to compare findings between studies. Similar to our study, the most recent trial used the same definition of frequent users (≥5 ED visits in past 12 months), was held in a country with universal health insurance coverage and privately delivered health care (Switzerland) and showed a trend towards reduced ED use which did not reach statistical significance [33]. In comparison, of the two case management trials which showed a statistically significant reduction in ED among frequent ED users, the first took place in the US [15], while the second, conducted in a country with universal health insurance (Sweden), used telephone-based case management, an arguably different intervention [16].…”
Section: Discussionsupporting
confidence: 57%
“…The high heterogeneity between studies, most importantly in how frequent users are defined, but also in participant demographic and clinical characteristics, the nature of the intervention (type and quality of case management) and system level-factors such as availability and accessibility of usual care services, may contribute to the lack of consistent findings and certainly limits the ability to compare findings between studies. Similar to our study, the most recent trial used the same definition of frequent users (≥5 ED visits in past 12 months), was held in a country with universal health insurance coverage and privately delivered health care (Switzerland) and showed a trend towards reduced ED use which did not reach statistical significance [33]. In comparison, of the two case management trials which showed a statistically significant reduction in ED among frequent ED users, the first took place in the US [15], while the second, conducted in a country with universal health insurance (Sweden), used telephone-based case management, an arguably different intervention [16].…”
Section: Discussionsupporting
confidence: 57%
“…Several studies reported that case management for medical aid beneficiaries was effective in reducing healthcare use [11][12][13][14]. However, most of these studies focused on reducing healthcare use to demonstrate the effectiveness of case management.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, adequate case management interventions could lead to fewer ED visits by frequent users by improving ACSC management, as well as through the orientation and coordination of healthcare services. 30 The present study has some notable strengths. First, it was carried out with an exhaustive medico-administrative database of older adults in Quebec, Canada, making the results generalizable to our whole population of interest.…”
Section: Discussionmentioning
confidence: 89%
“…To control costs and ensure the highest quality of care, we must meet the needs of geriatric patients in the ED and also across the care continuum. As an example, adequate case management interventions could lead to fewer ED visits by frequent users by improving ACSC management, as well as through the orientation and coordination of healthcare services …”
Section: Discussionmentioning
confidence: 99%